Analisis Konsep 3a Dalam Pengembangan Wisata Kota Tua - Rizki Nurul Nugraha; Prama Hardika (Peneliti.net, 2023)
This study aims to analyze the 3A concept and conclude the SWOT concept in the development of Kota Tua tourism in Pinangsia Village, Tamansari District, and West Jakarta Municipality. This research uses a qualitative-descriptive approach to research. The informants in the study were the chairmen of the Kota Tua bicycle rental community and visitors to Kota Tua, namely Mr. Cevi and Firmansyah Syahputra. This research used field observation, interview, and library research methods. The analysis technique used is Miles and Herberman's interactive analysis method and SWOT analysis. The results found are Education on the history of Jakarta and being a place for tourists to relax, Kota Tua Tourism is one of the historical tours in Jakarta as a historical tourist spot. One of the attractions are several museums and cafes with European nuances. The Jakarta Kota Museum and Batavia Café are tourist icons in the Old City Region. There are a number of other supporting tourist objects that have great potential.